PERAN PEREMPUAN DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI UMKM BERBASIS PENGETAHUAN KHAS PEREMPUAN DI WILAYAH DKI JAKARTA - Eva Reviana; Khalisah Visiana Subekti (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to be able to increase MSMEs in the culinary sector because it involves the role of women and the typical knowledge possessed by women in DKI Jakarta. The population in this study is 1,157 MSMEs in the DKI Jakarta Region and MSMEs in the culinary sector. Sampling in this study was carried out by purposive sampling technique with the number of samples obtained 112. The software used in the study to analyze the data was SmartPLS v.4. The results of this study show that 1) women's distinctive knowledge has a significant effect on the role of women in community economic empowerment. 2) women's distinctive knowledge has a significant effect on MSMEs, because women's distinctive knowledge has an important role in improving MSMEs. 3) MSMEs have a significant influence on the role of women in community economic empowerment. 4) MSMEs mediate the relationship between women's distinctive knowledge and the role of women in community economic empowerment.